2 - Vers une redéfinition de la construction sociale et psychologique de la femme parallèlement à la célébration de la Journée Internationale de la Femme au Cameroun - NZINO MUNONGO Victorine Ghislaine, (Identity, Culture and Politics, 2018)
Redefining the social and psychological construction of women while celebrating the International Women's Day in Cameroon Since the adoption of international texts in favour of women, construction and deconstruction of paradigms of gender became global. In 30 years celebration, International Women's Day both internationally and nationally the women 'right to decide became the new rule. Nevertheless, no society did not identify yet women as 'power-holders', as having control over 'power' and as exercising 'power for their own benefit. In Africa, main issues are freeing the woman from the absolute subordination assigned by the patriarchal society and extending her field of activity beyond reproduction, production and management. What about Cameroon? This contribution will study present-day Cameroonian patriarchal society and the place of women and the celebrations of International Women's Day. This study will be based on qualitative and quantitative data. Referring to the stakeholder approach, the focus of the analysis will be on understanding the power dynamics between the parties, interests and needs of each other in order to determine a concession that brings satisfaction to the different Parties.